Tradisi Ziarah Kubur dalam Masyarakat Indonesia: Antara Kearifan Lokal dan Ancaman Kemurnian Tauhid - Sarah Novian Chand; Fadia Raihan Aqrandista; Lintang Asmaradana; Rafi Almas Izzatullah; Dadan Firdaus; Muhammad Rafif Athallah (Jurnal Teologi Islam, 2025)
The tradition of grave visitation (ziarah kubur) has long been an integral part of the religious culture of Indonesian Muslims. Islam views this practice as a recommended (sunnah) act to remind believers of death; however, in practice, deviations often occur that potentially undermine the principle of tawhid. These deviations include acts such as seeking blessings, believing in the mystical power of saints’ or scholars’ graves, and performing khurafat rituals. This research aims to describe the practice of ziarah kubur in Indonesia, identify elements that deviate from the principle of tawhid, and offer theological solutions based on Islamic monotheism. Using a qualitative approach and literary. Review method, the research analyzes classical and contemporary Islamic literature. The findings show that deviant practices, such as making requests to the deceased and offering ritual sacrifices, fall under the categories of shirk jali (overt polytheism) and shirk khafi (hidden polytheism), both of which contradict the core tenets of tawhid. These deviations not only affect individual faith but also contribute to the formation of a misguided religious culture in society. Therefore, an educational approach through dakwah (Islamic preaching) is needed, involving both religious and cultural leaders, to ensure that ziarah is carried out wisely—retaining its spiritual value without violating Islamic creed. The limitation of this study lies in its theoretical nature, as it does not include empirical fieldwork. The implication of this research suggests the need for collaboration between religious education and cultural preservation to maintain the practice of ziarah in line with Islamic teachings and guidance